Analisis Akuntansi Utang Transfer Ke Daerah Dan Dana Desa Pada UAPBUN Ba-999.05 - Deni Herdiyana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The study was conducted to analyze the implementation of payable accounting for transfer to the regions and village funds, and also comparing the accounting standards regarding transfers to the regions and village funds with the implementation carried out by UAPBUN BA-999.05. The research method used is a qualitative approach, namely literature study and descriptive analysis.The conclusion of the study is that in general the recognition, measurement, recording, presentation and assessment of TKDD have referred to the applicable regulations. However, there are differences in the recording of accounts for TKDD payables transactions. Keywords: UAPBUN BA-999.05; transfers to regions; village funds; TKDD payables